Experimentation of PBL and PJBL Learning Models on Junior High School Students' Mathematical Problem-Solving Ability in Driving Schools - Setiani, Ana; Yulianti, Yulianti; Agustiani, Nur; Septiani, Eka; Muhassanah, Nur'aini (PRISMA, 2025)
When preparing a lesson plan, teachers should consider their mathematical problem-solving skills because this study aims to determine the mathematical problem-solving ability of junior high school students in driving schools that use teaching modules with PBL, PJBL, and conventional learning model stages in the independent curriculum. The research method used in this study is Quasi-Experimental with a Pretest-Posttest Control Group Design research design. The population in this study is all grade VII students of SMPN 1 Bantargadung, which totals 72 students, and the sample is divided into three classes. The sampling technique used in this study is Cluster Random Sampling. The question instruments used were in the form of three questions on mathematical problem-solving skills in social arithmetic material and observation sheets. The results of the study showed that there was a difference in the problem-solving ability of junior high school students who used the PBL learning model with the PJBL learning model, and the conventional learning model of the independent curriculum, PBL learning was better compared to the PJBL learning model on the problem-solving ability of junior high school students, the traditional learning of the independent curriculum was better than the PBL learning model on the problem-solving ability of junior high school students,  and conventional learning of the Independent curriculum is better than the PJBL learning model on the problem-solving ability of junior high school students.